Grygiel, Marcin and Laura A. Janda. eds. 2011. Slavic Linguistics in a Cognitive Framework. Frankfurt am Main, Berlin, Bern, Bruxelles, New York, Oxford and Wien: Peter Lang - Stanojević, Mateusz-Milan (Array, 2011)
This is a review of the book: Grygiel, Marcin and Laura A. Janda. eds. 2011. Slavic Linguistics in a Cognitive Framework. Frankfurt am Main, Berlin, Bern, Bruxelles, New York, Oxford and Wien: Peter Lang.